THE REPRESENTATION OF CONTESTED PERSPECTIVES IN THE FILM "NAGABONAR JADI 2": A STUDY OF SOCIAL DEVELOPMENT - Tamba, Dumanita; Tamba, Wahyu Pratama (Progress In Social Development, 2025)
Film, as an entertainment and educational medium, has a unique role in reflecting social reality. Although the film “Nagabonar Jadi 2” explicitly features a variety of social issues, an in-depth understanding of the underlying dynamics and their implications for social development is often not fully articulated. This research chooses a descriptive qualitative approach in abstracting and analyzing the film, using scene and storyline observations and the theoretical framework of social development. This research highlights the absence of social development reflections in Indonesian films as a medium for critical education of society. The analysis shows that the film effectively represents the contestation of fundamental views between traditional values (Nagabonar) and modernity (Bonaga). This contestation is manifested in issues such as land use conflict (family grave), urban-rural divide, access to education, cultural shift, and public service integrity. The discovery that these social issues are more appropriately identified as “contestation of perspectives” is a distinct contribution to the field of social development studies, offering a new perspective in analyzing films as objects of development studies. From a social development perspective, this contestation underscores the urgency of a holistic approach, respect for local wisdom, enhancement of human and social capital, and public-private synergy for an inclusive and equitable development.